Lacking Liberation in Language: African American Language in the Animated Film The Secret Life of Pets - Rebekah May Degener (CLELEjournal, 2017)
This paper is in three parts. I begin with an introduction to the concept of African American Language (AAL), discussing its position in American society in relation to the hegemony of Standardized American English. I then explore the use of AAL in Illumination Entertainment's The Secret Life of Pets (2016). The characters' code-switching to AAL in the film is problematized, and I argue that AAL is utilized to mark animated characters as both deviant and belonging to a lower socio-economic class. Furthermore, I assert that AAL is used to introduce issues of social inequality, issues that by the end of the film appear unimportant by a central character's realization that his claims of social inequality are unsubstantiated. Thus, the film attempts to silence both AAL and the pleas for equality expressed through Black Language. Finally, this paper highlights the ways that The Secret Life of Pets works to shape viewers', students' and teachers' attitudes towards African American citizens and the legitimacy of AAL.